THE ROLE OF THE RUSSIAN ORTHODOX CHURCH OF THE MOSCOW PATRIARCHATE IN THE PEACEKEEPING MOVEMENT: PRACTICE AND THEOLOGICAL JUSTIFICATION - Olga K. Shimanskaya (Научно-аналитический вестник Института Европы РАН)
The birth of the peacekeeping movement in the post-war period was caused by the consolidation of all humanistic forces against the threat of a new possible world conflict with the use of nuclear weapons in the context of the formation of a bipolar system of international relations and the formation of new opposing military-political blocs. The purpose of the article is to understand the role of the Russian Orthodox Church in the Soviet and world peacekeeping movement, both secular and Christian, and to trace its main stages and forms. To identify the motives that guided the representatives of the Church when they were active in peacekeeping and what results they achieved. In the 50-60s of the twentieth century, the Russian Orthodox Church became a fullfledged participant in the horizontal civil struggle for peace, which met the needs of its clergy and flock who had gone through the trials and tragedy of the Great Patriotic War (1941–1945). The hierarchs of the Church joined all Soviet organizations of the corresponding profile. The Russian Orthodox Church became a member of the World Council of Peace Supporters, the Christian Peace Conference, the Conference of European Churches, advocating for the strengthening of peace in Europe. Peacekeeping as a sphere of cooperation between the practical policy of the Soviet state and church activity receives a Christian, Orthodox assessment, and its result is the development of a «theology of peace». Thus, the peacekeeping activity of the Church modifies the established traditionalism, and in many ways modernizes it in the spirit of the demands of the tim